On the influence of workpiece material on friction in microforming and lubricant effectiveness - Taureza, Muhammad (2014)
The frictional behaviors between metal forming tool and three different metallic materials were evaluated using the modified T-Shape test. A mathematical function is proposed to describe the calibration curves for different friction coefficients. Round bars of copper, aluminum and silver of diameter 1 mm and length 5 mm were used as the workpieces to study the material influence on friction factor, m, during unlubricated microforming process through comparison between simulation and experimental results. Furthermore, various lubricants were used with the aluminum and copper to examine their performance in microforming. The results have shown that the workpiece materials not only determine the friction factor, m, during unlubricated microforming, but also influence the performance of lubricants. Lubricant can be completely ineffective and may not produce discernible friction reduction in microforming, unlike in conventional metal forming. By considering the influence of contact pressure on lubricant effectiveness, a novel pressure dependent frictional model and a lubricant evaluation method are proposed.